The Happiness of the Katakuris - Miike, Takashi; Yamamoto, Hideo; Sawada, Kenji; Matsuzaka, Keiko; Takeda, Shinji (Tartan Video, 2003)
Totally bizarre (and thus in keeping with Miike's other work), "The Happiness of the Katakuris" tells the story - as a musical - of an innkeeping family that hits a string of bad luck with its very first patron turns up dead. So they bury him out back, so word doesn't get out and ruin the business before it ever gets going. Apparently a remake of a Korean film I've never seen, the oddity of the plot is matched only be the strangeness of the singing. There's claymation, dance numbers, dancing corpses, and bizarre cross-dressing karaoke. How can you not be enthralled? How can you not be baffled completely? [www.filmcritic.com]
Keywords: DVD-Video